2021
DOI: 10.1128/mbio.01819-21
|View full text |Cite
|
Sign up to set email alerts
|

The dCache Chemoreceptor TlpA of Helicobacter pylori Binds Multiple Attractant and Antagonistic Ligands via Distinct Sites

Abstract: Numerous chemotactic bacterial pathogens depend on the ability to sense a diverse array of signals through chemoreceptors to achieve successful colonization and virulence within their host. The signals sensed by chemoreceptors, however, are not always fully understood.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…Our results reinforce the idea that dCache domains are able to bind a large diversity of ligands. Although many of them have been proved to bind amino acids, some dCache‐containing chemoreceptors have been shown to bind other kinds of molecules, such as lactate, fumarate, malate, polyamines, histamine and benzoate derivatives [29,35,48–50]. Surprisingly, SO_1056 dCache shares similarities with the PctA chemoreceptor described to bind amino acids, while S. oneidensis does not show any chemotactic behaviour towards amino acids [20].…”
Section: Discussionmentioning
confidence: 99%
“…Our results reinforce the idea that dCache domains are able to bind a large diversity of ligands. Although many of them have been proved to bind amino acids, some dCache‐containing chemoreceptors have been shown to bind other kinds of molecules, such as lactate, fumarate, malate, polyamines, histamine and benzoate derivatives [29,35,48–50]. Surprisingly, SO_1056 dCache shares similarities with the PctA chemoreceptor described to bind amino acids, while S. oneidensis does not show any chemotactic behaviour towards amino acids [20].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the primary cytokines include: 1) IL-17A, which promotes neutrophil recruitments through IL-8 and promotes the expression of antimicrobial peptides from epithelial cells; 2) IL-17F, which upregulates the expression of other pro-inflammatory cytokines and chemokines, inducing IL-2, TGF-β, IL-6, and GM-CSF; 3) IL-21, which promotes the proliferation of Th1 and Th17 cells, creating a positive feedback loop, and promote the proliferation of B-cells; and 4) IL-22, which acts on non-hematopoietic cells by upregulating antimicrobial peptide expression and promoting tissue repair (51). Interestingly, recent work has shown that arginine, a TlpA chemoattractant (25), and the polyamine pathway are critical for maintaining Th17 pathogenicity (54). Both of these factors drive Th17 cells toward a pro-inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems that loss of tlpA results in strains that are less able to thrive in the antrum and more able to thrive in the corpus. It is possible that TlpA’s signals—arginine, cysteine and fumarate (25)— are critical in the antral glands and therefore tlpA mutants cannot access these ligands efficiently and do not grow as well as WT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is now a significant body of evidence for the existence of naturally occurring signal antagonists (Busch et al ., 2007; Martin‐Mora et al ., 2018; Johnson et al ., 2021), which are compounds that bind to the same site as the signal molecules but fail to induce downstream signalling (Fig. 2) – a phenomenon likely due to different conformational changes induced by signal and signal antagonist binding (Koh et al ., 2016).…”
Section: Antagonists Targeting Signal Transduction Systems In Anti‐in...mentioning
confidence: 99%